Integrated Design of Emergency Medical and Material Distribution Networks During the Epidemic Outbreak Period - Xiaoping Li; Gefeng Lu; Qing-Mi Hu; Jiayun Lu (IEEE Access, 2023)
During the epidemic outbreak period, the number of infected people increased explosively. In order to effectively contain the further spread of the epidemic and treat infected people, it is necessary to make reasonable planning for the treatment of infected people and the distribution of materials. In this paper, a multi-objective mixed-integer programming model for the integrated design of emergency medical and material distribution networks is developed, in which the location of medical points, the allocation of infected people, and the distribution of medical materials are addressed in the multi-stage planning. Then, the multi-objective model is solved by the augmented $ε $ -constraint method. A realistic case study on Huangpu District of Shanghai in China is conducted to demonstrate the validity of the developed model. The results show that the integrated consideration of the emergency medical network and the material distribution network is more capable of reducing the total transportation distance and decreasing the total operating cost.